The Mission in Sightː How a Leaders' Motivation and Awareness relates to their Followers' Mission Valence - Marcel Mayr (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2019)
The organizational mission can function as a major asset in recruiting and motivating employees in public service organizations. However, it is up to the respective team leaders to encourage their follower's perception of the mission's attractiveness. Therefore, this article examines a leader's awareness of his or her follower's level of mission valence. Based on responses from 86 team leaders and 414 team members, the results of the multilevel analysis indicate that leaders that are more aware of mission valence breed teams that are more receptive of the organizational mission. Moreover, a leader's extrinsic motivation weakens the relationship between leader-perceived and memberperceived mission valence, while intrinsic motivation shows no sign of interaction. In terms of practical implications, the results illustrate that leaders should be encouraged to utilize their awareness to deliberately apply leadership practices that enhance the attractiveness of the mission for their team. Implications for theory include the notion that mission valence can be meaningfully conceptualized as a multilevel phenomenon.
Keywords: 330; mission valence; self-other agreement; intrinsic motivation; extrinsic motivation; multilevel analysis; public and nonprofit organization